Persistent postpartum urinary retention following vaginal delivery: a rare complication in obstetrics practice - Chaurasia, Amrita; Tyagi, Kamini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Postpartum urinary retention occurs in 10-15% of women and is likely to be multifactorial in origin. Long labour, epidural analgesia, instrumental delivery, nulliparity, significant vaginal and perineal laceration or a previous history of voiding difficulty are risk factors for altered voiding parameters. Previous literatures have defined two types of urinary retention, first, overt retention and the other covert variety. Overt variety represents the acute retention while covert variety is of subacute in nature. Being subacute in nature, it damages the detrusors slowly. Sometimes the damage is so much so that it may take substantial time to recover or may not recover at all and the patient may have lifelong detrusor hypotonia with persistent urinary retention, requiring lifelong intermittent self-catheterization. This badly affects her personal as well as social wellbeing and also poses her for recurrent urinary tract infection. Here, we report a case of 25 yrs old, 36 weeks primigravida having persistent postpartum urinary retention following vaginal delivery, Who was enough fortunate to have recovery of detrusors. But, still it took 3-4 weeks for complete recovery of the urinary bladder.